2011
DOI: 10.1088/0029-5515/51/10/103027
|View full text |Cite
|
Sign up to set email alerts
|

Initial phase wall conditioning in KSTAR

Abstract: Initial phase wall conditioning in KSTAR is depicted. The KSTAR wall conditioning procedure consists of baking, Glow Discharge Cleaning (GDC), ICRH Wall Conditioning (ICWC), and boronization (Bz). The vessel baking has been performed in order to remove various kinds of impurities including H 2 O, carbon and oxygen for the plasma. The total outgassing rates in the KSTAR campaigns are compared. GDC is regularly performed as standard wall cleaning procedure. Another cleaning technique is ICWC, which is useful for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For a machine equipped with superconducting coils, ICRH or ECRH wall conditioning (ICWC or ECWC) would be a mandatory choice. Wall conditioning with ICWC between shots is performed regularly to have a better wall condition and density control [4]. Table 1 tabulates the technical specifications and the current achievements of KSTAR, actively preparing for its long-pulse mission step by step to become one of the promising candidates for ITER pilot devices.…”
Section: Device Updatesmentioning
confidence: 99%
“…For a machine equipped with superconducting coils, ICRH or ECRH wall conditioning (ICWC or ECWC) would be a mandatory choice. Wall conditioning with ICWC between shots is performed regularly to have a better wall condition and density control [4]. Table 1 tabulates the technical specifications and the current achievements of KSTAR, actively preparing for its long-pulse mission step by step to become one of the promising candidates for ITER pilot devices.…”
Section: Device Updatesmentioning
confidence: 99%
“…Remarkably the occurrence of a well-defined lipomatous mass juxtaposed to another nonlipomatous mass (type III), as seen in our case, is described in only 1 of the 15 patients; moreover, the only case of DDLS with osteosarcoma of this study showed a morphology of type I, but not type III. 13 In our DDLS on CT images the most relevant elements in the context of the osteosarcomatous component were diffuse and coarse calcifications.…”
Section: Discussionmentioning
confidence: 69%
“…Plasma-surface interaction is one of the critical issues for ITER. Carbon-based low Z materials have been the most commonly used plasma-facing components (PFCs) in conventional tokamaks for a long time [146][147][148]. Recently, JET [149] and ASDEX Upgrade [150] have employed beryllium and full tungsten first walls for ITER-relevant wall conditions [149,150].…”
Section: Plasma-surface Interactionmentioning
confidence: 99%